Vowel acoustics of Nungon child-directed speech, adult dyadic conversation, and foreigner-directed monologues - Sarvasy, Hannah S.; Li, Weicong; Elvin, Jaydene; Escudero, Paola (Frontiers in Psychology, 2022)
In many communities around the world, speech to infants (IDS) and small children (CDS) features special acoustic and prosodic features, compared to speech directed at adults (ADS), including: increased mean pitch, increased pitch range, increased vowel duration, and vowel hyper-articulation. Some of these are also attested in foreigner-directed speech (FDS), which has been studied for a smaller range of languages, generally major national languages, spoken by millions of people. We examined vowel acoustics in CDS, conversational ADS, and monologues directed to a foreigner (possible FDS, labeled MONO here) in the Towet dialect of the Papuan language Nungon, spoken by 300 people in a remote region in northeastern Papua New Guinea. Previous work established that Nungon CDS entails optional use of consonant alteration, special nursery vocabulary, and special morphosyntax. This study shows that Nungon CDS to children aged 2;2–3;10 lacks vowel hyper-articulation, but still displays other common prosodic traits of CDS styles around the world: higher pitch and pitch range. A developmental effect was also attested, in that speech to two-year-olds contained vowels that were significantly longer than speech to three-year-olds, which in turn had similar duration to vowels in Nungon ADS. Finally, we compared the acoustics of vowels in Nungon CDS and conversational ADS to vowels in monologue narratives, produced with a non-native Nungon speaker as primary listener. The vowel triangles of these monologues were significantly larger than those of either CDS or conversational ADS, indicating vowel hyper-articulation. Mean pitch and pitch range in the monologues, compared with CDS and conversational ADS, differed among women and men, possibly relating to cultural expectations of female and male storytelling and conversational styles. The Nungon pattern may align with the patterns of vowels in Norwegian IDS, CDS, and FDS, where hyper-articulation is found in FDS, but not CDS or IDS.